KAJIAN KAMPANYE SOSIAL WORLD WILDLIFE FUND: THE LAST SELFIE - Egie E. Yusadhi; Mansoor, Alvanov Zpalanzani (Institut Bisnis dan Teknologi Indonesia, 2020)
The cases of protecting endangered animals around the world are difficult to solve. Lack of public awareness of the survival of these animals become one of the contributing factors. Given the importance of the survival of these animals, World Wildlife Fund as a global fund-raising agency invitesDanish and turkey advertising agencies to create a social campaign where they invited millennials to donate their money to help the survival of endangered animals and comes up with #LastSelfie. It is social media based campaign using Snapchat which then integrated with other social media. This campaign generated 40,000 tweets in a week and meets donation goal in just three days. This is a descriptive explanative research which itspurpose is to find out whether #LastSelfie campaign through breaking the structure of campaign materials and depict its relationship with the aim of campaign based on copywriting and target audience Engagement Process in social media theory. Through the application of this concept which encompasses various aspects of the campaign, at the end of this writing, the authors concludes that #LastSelfie campaign corresponds to the process sequence of Engagement in social media — consuming, curation, creation, collaboration, through meticulous campaign naming, copywriting strategy, sharing among peers, and collaborative donation to help preserve endangered animals.